Clinical Effects of Rehabilitation on Balance in People With Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Canales-Díaz, María Belén; Olivares-Valenzuela, Carolina; Ramírez-Arriagada, Amanda; Cruz-Montecinos, Carlos; Vilaró, Jordi; Torres-Castro, Rodrigo; Núñez-Cortés, Rodrigo (Frontiers in Medicine, 2022)
Background Patients with chronic obstructive pulmonary disease (COPD) have systemic damage secondary to the primary pulmonary impairment, expressed in impaired peripheral musculature and a deficit in postural control compared to healthy subjects. This study aimed to determine the effects of rehabilitation on balance in patients with COPD. Methods An exhaustive search was conducted in four databases (Pubmed, Cochrane Library, EMBASE, Web of Science). Articles with a population of COPD receiving rehabilitation (therapeutic exercise, pulmonary rehabilitation, or physical therapy modalities) in an outpatient setting were included. Two independent reviewers selected and assessed the study quality. The risk of bias was assessed with the Cochrane Risk of Bias Tool for Randomized Controlled Trials. Results A total of eight studies involving 284 patients were included in the qualitative synthesis. The meta-analysis showed an overall result in favor of balance training for the Berg Balance Scale (mean difference 3.91 points; 95% CI: 1.51 to 6.31; P = 0.001), Timed Up and Go test (mean difference −1.58 s; 95% CI: −2.63 to −0.53; P = 0.003) and Unipedal stance test (mean difference 3.56 s, 95% CI: 2.58 to 4.54; P). Conclusion This meta-analysis revealed that rehabilitation improve static and dynamic balance in patients with COPD. Systematic Review Registration PROSPERO ID: CRD42020218367.